2019
DOI: 10.1124/mol.119.115808
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying the ErbB/MAPK Signaling Cascade as a Therapeutic Target in Canine Bladder Cancer

Abstract: Canine transitional cell carcinoma (TCC) of the bladder accounts for 2% of diagnosed canine cancers. Most TCCs are inoperable and unresponsive to traditional chemotherapy. Median survival time is typically less than a year for all treatments indicating a need for more effective therapies. Recent studies have discovered that approximately 70% of canine TCCs harbor mutations in the proto‐oncogene BRAF, a kinase involved in the mitogen‐activated protein kinase (MAPK) pathway that controls cell proliferation, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…A summary of the array results and observed differences in RTK phosphorylation between primary UC tumor samples and UC cell lines is provided in Table 2 . Unsurprisingly, greater than 85% of primary UC tumors demonstrated phosphorylation of EGFR (100%) and ErbB2 (89%) which is concordant with prior studies suggesting that overexpression of ErbB2 and EGFR is a common event in this cancer [ 22 , 23 ] and that alterations in ErbB2-mediatied [ 24 ] signaling pathways drive the proliferative phenotype in UC cells. In addition, we found that UC tumors showed phosphorylation of insulin receptor (78%), ROR1 (89%), ROR2 (89%), Tie-1 (100%), and Tie-2 (78%), with members of the FGFR family of receptors occurring less frequently (FGFR1 44%, FGFR2 44%, FGFR3 44%, and FGFR4 22%).…”
Section: Resultssupporting
confidence: 85%
“…A summary of the array results and observed differences in RTK phosphorylation between primary UC tumor samples and UC cell lines is provided in Table 2 . Unsurprisingly, greater than 85% of primary UC tumors demonstrated phosphorylation of EGFR (100%) and ErbB2 (89%) which is concordant with prior studies suggesting that overexpression of ErbB2 and EGFR is a common event in this cancer [ 22 , 23 ] and that alterations in ErbB2-mediatied [ 24 ] signaling pathways drive the proliferative phenotype in UC cells. In addition, we found that UC tumors showed phosphorylation of insulin receptor (78%), ROR1 (89%), ROR2 (89%), Tie-1 (100%), and Tie-2 (78%), with members of the FGFR family of receptors occurring less frequently (FGFR1 44%, FGFR2 44%, FGFR3 44%, and FGFR4 22%).…”
Section: Resultssupporting
confidence: 85%
“…In our study, KEGG pathway analysis of differentially expressed lncRNA, mRNA, circRNA, and miRNA shows that BMP9 treatment is involved in the cell cycle, focal adhesion, chemokine signaling, and the ErbB signaling pathway. These pathways are related to the MAPK signaling pathway [88], differentiation and angiogenesis [89], and the PPAR signaling pathway, which is involved in lipid metabolism and adipocyte differentiation [90].…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure 1C, the biological functions of these miRNA candidates were significantly involved in cancer-related signaling pathways, including those of proteoglycans in cancer, MAPK, TGF-beta, FoxO, colorectal cancer, cellular senescence, the adherens junction, PI3K-Akt, Hippo, autophagy, focal adhesion, and ErbB. Some of these signaling pathways have been reported to have a biological function in bladder cancer progression [29,30].…”
Section: Microrna Profiles Were Generated By Next-generation Sequencingmentioning
confidence: 97%